Skill Level of Control Passing, Dribbling and Shooting Futsal in Extracurricular Participants of Public Elementary School 1 Guntung Payung Banjarbaru - Fia Sofia; Ramadhan Arifin; Lazuardy Akbar Fauzan (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine the level of passing control, dribbling and shooting futsal skills in extracurricular participants of Public Elementary School 1 Guntung Payung Banjarbaru. This research method is descriptive quantitative with a test measuring passing control, dribbling and shooting skills in extracurricular participants of Public Elementary School 1 Guntung Payung Banjarbaru. The results of the analysis of the passing control research with a low category of 13.33%, medium 73.33%, high 13.33%. The results of the analysis of the dribbling research with a low category of 0.00%, medium 80.00%, high 20.00%. The results of the shooting research analysis with low category 13.33%, medium 73.33%, high 13.33%. The conclusion of the results of the futsal control passing research on extracurricular participants of Public Elementary School 1 Guntung Payung Banjarbaru is “moderate”. The conclusion of the results of the futsal dribbling research on extracurricular participants of Public Elementary School 1 Guntung Payung Banjarbaru is “high”. The conclusion of the results of the futsal shooting research on extracurricular participants of Public Elementary School 1 Guntung Payung Banjarbaru is “moderate”. It can be concluded from the three instruments above that the level of control passing, dribbling and shooting skills of extracurricular participants of Public Elementary School 1 Guntung Payung Banjarbaru is in the “moderate” category.